Answer:
x = 8, and y = 0
Explanation:
We can solve this by taking y as (x-8), as it states there.
Since y is equal to x-8, we can rearrange the system of equations into one single equation.
We can multiply y by 8, as it shows in the first equation, which is something like 8x-64.
Since it is a negative 8 being multiplied by y, it would be the inverse of 8x-64, which is -8x+64.
We can now organize our equation here.
3x - 8x + 64 = 24.
We can use subtraction property of equality by subtracing 64 from both sides to get rid of it.
We will get something like:
3x - 8x + 64 - 64 = 24 - 64.
Simplify by solving like terms like the x value and the integers.
-5x = -40
Divide both sides with division property of equality:
-5/5x = -40/5
x = 8
We can then plug the 8 back into x, lets use the second equation because I'm lazy and it looks the easiest to solve for.
y = (8) - 8
y = 0
Therefore, x = 8, and y = 0.